AVALIAÇÃO DO USO DE AGREGADOS MIÚDOS RECICLADOS NA DOSAGEM E PRODUÇÃO DE CONCRETOS RECICLADOS - Santana, Valquiria; Leite, Mônica (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The main goal of this work is to evaluate the mix design of concrete with 20 and 40% of recycled fine aggregate (RFA), using the Graff's table flow test for two flow levels (355 ± 5mm and 405 ± 5mm). The results show that the adapted IPT mix design method can be used for recycled concrete, provided that some parameters are considered, such as : the use of the Graff's table flow test to determine the workability; the use of low proportions of AMR; and an increase of the ideal dry mortar content with the increase of RFA proportion.